Knowledge about Cervical Cancer and Awareness of Human Papillomavirus (HPV) and HPV Vaccine among Female Students from Serbia - Nataša K. Rančić; Milan B. Golubović; Mirko V. Ilić; Aleksanda S. Ignjatović; Radomir M. Živadinović; Saša N. Đenić; Stefan D. Momčilović; Biljana N. Kocić; Zoran G. Milošević; Suzana A. Otašević (Medicina, 2020)
Background and objectives: Persistent infection with carcinogenic human papillomavirus (HPV) is the leading cause of cervical cancer. The study explored students’ knowledge about cervical cancer and awareness of human papillomavirus and the HPV vaccine. Materials and Methods: A questionnaire-based survey was carried out among 1616 first-year female college students at the University of Niš. It examined socio-demographic characteristics, measured the score of knowledge about cervical cancer, assessed awareness regarding HPV and the HPV vaccine and inquired about the source of information about cervical cancer and HPV. Results: The average cervical cancer knowledge score was 16.35 ± 7.92 (min 0, max 30), with medical professional education, parents’ education level, place of residence and relationship status having significant effects on the score. The awareness about HPV and the HPV vaccine was low, with only 14.2% of students having heard about both HPV and its vaccine. The most commonly reported sources of information were the media, while the most competent one was organized health education. Conclusions: Health promotion campaigns and educational programs are necessary in order to reduce cervical cancer burden and should be directed particularly towards those who have demonstrated low cervical cancer knowledge and low awareness regarding HPV and its vaccine.